Marketing of Pina fiber in Balete, Aklan. - Barrios, Jerson Torre
This study describe and analyses the different marketing channels, functions, costs, margins, and the different problems encountered by both producers of pina and middlemen of pina fiber in Balete, Aklan. Of the four barangay sampled, primary data were obtained from ten (10) producers who were asked about their recent harvest, and 34 middlemen were consequently interviewed based on their last weeks's operations., Results of the study show that out of the 40,200 pina harvested by producers, scrappers absorbed the bulk or 69.71 (24,900), while the least fraction of .99 was taken by the producer-scraper-trader. Highest prices paid for pina at P0.35 was accorded by producer-scraper-knotter while scraper-knotters offered the least price at P.25. Despite of the five marketing activities performed, and corresponding costs on marketing investments, producers still incurred positive financial net farm price of P1.217. By marketing functions, seven types of middlemen were observed, namely: scrapers, producer-scrapers, scraper-knotters, producer-scraper-knotter, knotters, producer-scraper-trader, and traders---who essentially perform an overlap of functions. Though all types of middlemen incurred positive gross margin, not everyone experienced positive net margins and net returns. With the bulk of transactions disposed by traders (1,668.125) and producer-scraper-trader (2,000), these two types of middlemen received positive financial net margins and returns. Of the different marketing problems cited, the majority of producers and middlemen were unanimous in pointing at low price of the product as their biggest constraint. Other than the need to increase the price, organizing a cooperative and support from the local government, this study suggests, that due to the duplication of function among types of middlemen, specialization on a particular function (e.g. scraper or knotter---alone) is a must in order to curb the circuitous and dragging flow of the product and lessen costs on labor.